Male African Elephant (Loxodonta africana) Behavioral Responses to Estrous Call Playbacks May Inform Conservation Management Tools - Caitlin E. O’Connell-Rodwell; Monica N. Sandri; Jodie L. Berezin; Jaquelyn M. Munevar; Colleen Kinzley; Jason D. Wood; Maggie Wiśniewska; J. Werner Kilian (Animals, 2022)
Driven by reproductive motives, male African elephants (Loxodonta africana) in musth often expand their home ranges to locate estrous females. This extended range, coupled with heightened aggression often observed in musth males, can be particularly problematic in regions where human-modified landscapes and elephant territories increasingly overlap. Several mitigation tools have been tested to resolve a wide range of human–elephant conflicts with varying degrees of success due to geographical disparities and habituation. We present findings on the potential application of estrous call playbacks in manipulating the behavior and movement of male elephants non-invasively, particularly mature musth adults and younger post-dispersal males, in Etosha National Park. Estrous vocalizations were presented across 26 experimental trials to mature musth adults (n = 5), mature non-musth adults (n = 6), and non-musth males belonging to younger, post-dispersal age classes (n = 8), with behavioral responses scored on a gradient scale from 0–1. Both mature musth adults and younger non-musth elephants were significantly more likely to respond with the highest intensity by approaching the acoustic source compared to mature non-musth adults that avoided the call. However, younger males tested in the presence of an older, higher-ranking male tended to react with a lower intensity than those tested alone. This result likely demonstrates the influence of social hierarchy and associations on male elephant behavior. We also observed a significant increase in physiological response, measured by defecation rate, across all male groups in response to the estrous call playbacks. Our findings suggest that using estrous calls as acoustic deterrents may effectively and non-invasively aid in reducing tension at the human–elephant interface, depending on the age, social context, and reproductive status of the male elephant.